Umrah Backpacker: Studies and Research Path - Maliha, Hasna; Rahayu, Solihah Sari (SMART Insight, 2024)
Backpacker Umrah exemplifies the flexibility, where pilgrims choose economical self-travel—adjusting schedules, transiting between countries for cheap flights, and sharing costs with others. This study aims to see the development of research on the topic